The Per Oral Endoscopic Myotomy (POEM) technique: how many preclinical procedures are needed to master it? - Hernández Mondragón, Oscar Víctor; Rascón Martínez, Dulce Maria; Muñoz Bautista, Aracely; Altamirano Castañeda, Maria Lourdes; Blanco-Velasco, Gerardo; Blancas Valencia, Juan Manuel (Endoscopy International Open, 2015)
Background and study aim: Per oral endoscopic myotomy (POEM) is a complex technique used in achalasia. Preclinical training is essential but little is known about the number of procedures needed. The aim of this study was to determine the number of procedures required to master POEM in an animal model.Patients and methods: This prospective comparative study was conducted in two swine models at a single institution in Mexico City between November 2012 and October 2014: Group 1 (G1) = 30 ex vivo and Group 2 (G2) = 20 live swine models. POEM was mastered after finishing the five steps without complications. Time, characteristics, and complications were recorded. Velocity of tunnelization and myotomy (VTM) was determined. Ex vivo analysis was done in G1 immediately after finishing POEM and at day 30 in G2.Results: A total of 50 POEM were done in both groups (G1 = 30, G2 = 20). The mean times were 90.17 min (G1) and 89.50 min (G2) (P = 0.92). Myotomy was faster in G2 (21.10 vs 27.97 min; P = 0.009) with a slightly slower tunnelization (40.35 vs 41.13 min; P = 0.86). Myotomy was longer in G2 (9.25 vs 8.83 cm; P = 0.26). VTM between the groups was similar (G1 = 0.159 vs G2 = 0.157 cm/min; P = 0.925). Complications were: mucosotomy (G1 = 18 %, G2 = 8 %; P = 0.430), mediastinal perforation (G1 = 12 %, G2 = 8 %; P = 1.0), and perforation at the gastroesophageal junction (GEJ) level (G1 = 16 %, G2 = 4 %; P = 0.149). Seven models in G2 presented minor bleeding and there was one death not attributed to the procedure. Mastery was obtained after 26 cases.Conclusions: We suggest that centers interested in learning POEM consider 26 procedures in animal models to master it before performing it in patients with achalasia.